POLICY STRATEGY OF MAPILLI KPHL IN POLEWALI MANDAR DISTRICT, WEST SULAWESI - Muhammad Sarif; Bramasto Nugroho; Dodik Ridho Nurrochmat (Universitas Andi Djemma Palopo, 2022)
The success of the Forest Management Units (KPH) development policy is determined by the effectiveness of policy implementation. This study aims to formulate an appropriate policy strategy to improve the effectiveness of KPHL Mapili policies. This research was conducted at KPHL Mapilli in Polewali Mandar District, West Sulawesi. Data collection uses in-depth interview techniques. Data analysis was carried out descriptively using the Edward III 1980 theory approach. The results showed that the implementation of KPHL Mapilli development policy was hampered due to limited human resources, budget constraints, and lack of communication between managers as well as understanding of the bureaucracy towards the KPHL policy. Based on the problems as previously mentioned, the strategies needed to develop KPHL Mapilli are 1) streamlining communication (2) improving the quality of human resources (3) developing commitment of authorized institutions in the management of KPHL Mapilli (disposition) (4) improving understanding of the bureaucracy and exit strategies in the development of KPHL Mapilli.